Respuesta :
There are a few ways to solve this, the simplest of which is probably factoring. Start by finding factors of C (10) that add up to be B (-2).
fac(10) { -10, 1 ; -5, 2 }
Well, there are no factors of 10 that can add to b - so we will use the quadratic formula.
(-b +- sqrt(b^2 - 4ac)) / 2a
where a = 1, b = -2, c = 10
b^2 - 4ac = (-2)^2 - 4(1)(10) = 4 - 40 = -36
-b +- sqrt(-36) / 2a
(2 +- sqrt(-36)) / 2
sqrt(-36)
sqrt(-1 * 36)
sqrt(-1) * sqrt(36)
i * 6
6i
2 + 6i / 2 ; 1 + 3i
2 - 6i / 2 ; 1 - 3i
Solutions: 1 + 3i, 1 - 3i
Answer:
x = 1± 3i
Step-by-step explanation:
x^2-2x+10=0
We can complete the square to solve by subtracting 10 from each side
x^2-2x+10-10=-10
x^2 -2x = -10
We need to add (2/2) ^2 to each side or 1
x^2 -2x+1 = -10 +1
x^2 -2x+1 = -9
The left side factors into (x- (2/2) ) ^2
(x-1) ^2 = -9
Take the square root of each side
sqrt((x-1) ^2 =± sqrt(-9)
x-1 = ±sqrt(-1) sqrt(3)
Remember the sqrt(-1) = i
x-1 = ± 3i
Add 1 to each side
x-1+1 = 1± 3i
x = 1± 3i